ANALISIS KETERAMPILAN LITERASI SAINS MAHASISWA DENGAN TOSLS - Degi Alrinda Agustina; Lili Rahmawati (Universitas PGRI Yogyakarta, 2021)
This study aims to analyze the scientific literacy skills of PGSD students at the University of Borneo Tarakan with the Test of Scientific Literacy Skills (TOSLS). TOSLS is a test that measures skills related to the main aspects of scientific literacy, namely recognizing and analyzing the use of investigative methods that lead to scientific knowledge and skills to organize, analyze, and interpret quantitative data and scientific information. This study uses qualitative research, namely by analyzing and describing the main aspects of student scientific literacy with TOSLS. The results showed that the students 'scientific literacy skills were still in poor criteria as indicated by the students' skills in understanding the method of investigation that led to scientific knowledge of 59.54%, and the skills of organizing, analyzing, and interpreting quantitative data and scientific information by 54.56%. The results of this research become the basis for further research with innovative learning models and teaching materials to improve students' scientific literacy.Â